Асортимент тропічних та субтропічних рослин в інтер’єрах м. Кривий Ріг та шляхи його збагачення - Boyko, L.I. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2012)
The analysis of the results of studing of taxonomical composition of tropical and subtropical plants is carried out in the interiors of different types in Krivy Rih. The decorative state of plants is examined and their composition use is evaluated. An increase of plant assortment and methods, use of them in phytodesign development is substantiated.